Developing fire detection system for chemical laboratories / Saeed Barzabadi Farahani - Saeed, Barzabadi Farahani (2014)
Fire detection system as a key component of fire protection and safety plan in chemical laboratories, aim to detect the unwanted presence of fire in order to provide responses to a deemed threat to people, property and environment. This project describes the system in detail from detectable fire products to implementation of a fire detection system for a chemical laboratory. The literature review discusses various factors that impact the reliability and accuracy of the fire detection system. It further explores the operation principals and applicability of system components to provide a method to properly select and design of fire detection systems. The concept of this project is to develop a fire detection system for chemical laboratories to minimize the risk and maximize the safety. To achieve these objectives, a step-by-step approach introduced and the system was implemented.